Catch and release: Hyporheic retention and mineralization of N‐fixing Nostoc sustains downstream microbial mat biomass in two polar desert streams. Issue 4 (3rd July 2018) - Kohler, Tyler J.; Stanish, Lee F.; Liptzin, Daniel; Barrett, John E.; McKnight, Diane M.
Abstract: Much work has been performed to investigate controls on nitrogen (N) uptake in streams, yet the fate of assimilated N is comparatively poorly resolved. Here, we use in‐stream fixed N as an isotopic tracer to study the fate of assimilated N in glacial meltwater streams. We characterized δ 15 N signatures of Oscillatorean, Chlorophyte, and N‐fixing Nostoc mats over the lengths of two streams, and transported particulate organic matter (POM) in one. POM was isotopically most similar to Nostoc, which always had values near the atmospheric standard (δ 15 N ≅ 0‰), suggesting N‐fixation. Other mat types were depleted upstream, and became progressively enriched downstream (plateauing at δ 15 N ≅ 0‰), indicating a shift in N source. These results collectively show that Nostoc ‐derived N is mobilized, mineralized, and increasingly assimilated downstream as more depleted glacier‐derived N is exhausted, demonstrating the importance of organic matter processing to balancing elemental budgets, and improving our understanding of nutrient cycling in lotic environments.